2016
DOI: 10.21037/jtd.2016.02.56
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of plasma microRNA expression profiles in a Chinese population occupationally exposed to benzene and in a population with chronic benzene poisoning

Abstract: Background: Circulating microRNA (miRNA) has attractive interests as a non-invasive biomarker of physiological and pathological conditions. Our study aimed to investigate the potential effects of chronic benzene poisoning (CBP) and benzene exposure on miRNA expression, and identify CBP-related miRNAs. Methods:In the discovery stage, we used a microarray assay to detect the miRNA expression profiles among pooled plasma samples from ten CBP patients, ten healthy benzene-exposed individuals and ten nonbenzene exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
13
0
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 49 publications
(38 reference statements)
0
13
0
3
Order By: Relevance
“…Similarly, individuals exposed to benzene at median concentrations of 120 lg=m 3 had significantly higher global levels of H3 lysine 4 trimethylation (H3K4me3) marks compared with a control group . Perturbations to miRNA (Bai et al 2014a;Yang Liu et al 2016) and lncRNA (Bai et al 2014b) expression have likewise been detected in pooled plasma (Yang Liu et al 2016) and peripheral Figure 1. Diagrammatical summary of epigenetic modes on action.…”
Section: Benzene-epigenome Perturbations At Low-level Exposuresmentioning
confidence: 82%
“…Similarly, individuals exposed to benzene at median concentrations of 120 lg=m 3 had significantly higher global levels of H3 lysine 4 trimethylation (H3K4me3) marks compared with a control group . Perturbations to miRNA (Bai et al 2014a;Yang Liu et al 2016) and lncRNA (Bai et al 2014b) expression have likewise been detected in pooled plasma (Yang Liu et al 2016) and peripheral Figure 1. Diagrammatical summary of epigenetic modes on action.…”
Section: Benzene-epigenome Perturbations At Low-level Exposuresmentioning
confidence: 82%
“…), вирусы и др. Как уже отмечалось, miR-638 также чувствительна к воздействиям средовых факторов на уровне метилирования CpG-сайтов и ее экспрессии [10][11][12][13] [34,35], в одном -наблюдалась обратная ситуация [36], что может быть связано с клиническими особенностями включенных в исследование пациентов. В частности, уровень экспрессии данной микроРНК был выше в выборке пациентов с тройным негативным раком молочной железы, чем у пациентов с другими формами рака молочной железы [34].…”
Section: гены-мишени Mir-638 их вовлеченность в метаболические пути unclassified
“…Изменение спектра и уровня микроРНК, эпигенетические модификации (включая метилирование ДНК) рассматривают как важные компоненты патофизиологии болезней, в том числе и в качестве «посредников» эффектов не-благоприятных средовых факторов, способствующих развитию заболеваний [6][7][8][9]. С этой точки зрения интерес представляет miR-638, которая чувствительна к воздействию различных биотических и абиотических агентов; при этом направленность изменения уровня этой микроРНК зависит от влияющих агентов, продолжительности воздействия и от типа клеток [10][11][12][13][14][15][16][17]. Так, установлен более низкий уровень miR-638 у лиц с хроническим отравлением бензолом, по сравнению как с не контактирующими (контрольная группа), так и с кратковременно контактирующими с данным веществом индивидами.…”
unclassified
See 1 more Smart Citation
“…It has been reported that specific miRNA profiles affecting PTEN expression are altered following benzene exposure (260)(261)(262). While many miRNAs regulate insulin signaling pathways, we only assayed the miRNAs reported to be affected by benzene exposure.…”
Section: Discussionmentioning
confidence: 99%